Islamic Poems by Rukun Nasution (1928-1998): Themes and Social Relevance - Asari, Hasan; Budianti, Yusnaili (Center for Research and Development of Religious Literature and Heritage, 2021)
This study analyzes two poems written by Rukun Nasution (1928-1998), namely Syair Pengajak Solat (Invitation to Prayer) and Doa/Syair Menjelang Pajar (Invocation/Poem before Dawn). This manuscript only came to the attention of the authors in 2018, and this is the first time the book of poetry is being studied and described. The main objective of this study is to analyze the content of the poems, with reference to their socio-religious relevance and some philological aspects. Rukun (the popular name of Rukun Nasution) wrote his poems in the 1960s using Latin script, and the fact he had no formal education other than a three-year of elementary school made his creative productivity more interesting. He presented his ideas in a well-structured text while applying the 'aa-aa' rhyme consistently. The poems contain Islamic messages, with prayer procedures being the most dominant theme. These poems are relevant to document religious information, disseminate Islamic teachings, while remains artistically creative.